A new species of Propebrevitrichia Kelsey (Diptera: Scenopinidae: Scenopininae) from Botswana - Winterton, Shaun L. (Zootaxa, 2005)
Propebrevitrichia Kelsey is an endemic southern African genus of window-flies with distinct Gondwanan origins. Propebrevitrichia serowensis sp. n. is described and figured from Botswana.